The Role of Women towards Political Participation in Nigeria - Suleiman, Ibrahim (American Economic & Social Review, 2017)
This study investigates the factors that limit women’s participation in Nigeria’s politics using case study period between 1999 and 2015, among these factors are socioeconomic development, the country’s cultural heritage, historical legacies and institutional designs. The study employs secondary source as a method ofdata collection. The study reveals that the patriarchal system and male domination of the society, which relegates women to subordinate role, has created women’s inferiority complex and alienated them from the mainstream politics in Nigeria. The Nigerian political culture of thuggery and gangsterism has   made the political terrain too dangerous for most women to venture into mainstream politics. Besides, the stigmatization of women politicians by fellow women discourages the political participation of the former while religious beliefs and institutional arrangements that restrict women to family responsibilities in the country coupled with lack of genuine and decisive affirmative action to encourage women’s political participation, have created a legacy that limit women’s political participation in the country as a whole. Consequently, the study emphasizes the need to address those factors that entrench women subordination in Nigeria’s politics. These include, among others, the reformation of all religious, statutory and customary laws and practices that perpetuate women’s subordination in the country and the explicit specifications and modalities of affirmative actions on women’s political participation and clear guidelines for implementations in the Nigeria constitution.